Ações Estatais ou Políticas Públicas? Fronteiras, Fluxos Migratórios e Política Migratória - José Renato de Campos Araújo; Paula Vitória Pereira; Bryan Zelmar Sempertegui Rodas (Confins)
Based on reflections on the different realities of the Brazilian State, between two federal levels (federal and municipal government), this text reflects on the state of the arts of Brazilian Public Policies related to the international migratory flows that are directed to the territory in recent years. At the federal level, the text reviews the uncoordinated performance of the Brazilian State in relation to the flow of Venezuelans who enter Brazil through the border located in the state of Roraima, through the municipality of Pacaraima. At the municipal level, City Hall of the Municipality of São Paulo, from observations collected in field research actions at the Municipal School of Early Childhood Education Duque de Caxias, describes how the action of "Street Bureaucrats" are fundamental in the "construction" of actions of the Brazilian state for the migrant populations established in the territory of the country. We conclude on the relevance of this research agenda for consistent reflections on the state of the arts of Brazilian Public Policies.